UNIT 14.34 Murine Models of Helicobacter (pylori or felis)‐associated Gastric Cancer. Issue 1 (1st June 2015) - Duckworth, Carrie A.; Burkitt, Michael D.; Williams, Jonathan M.; Parsons, Bryony N.; Tang, Joseph M.F.; Pritchard, D. Mark
Abstract : Gastric adenocarcinoma is the fifth most common cancer and third most common cause of cancer‐related death in the world. The majority of these cancers develop in genetically susceptible individuals who are chronically infected with the Gram‐negative bacterium Helicobacter pylori . Often these individuals have also been exposed to certain environmental factors that increase susceptibility, such as dietary components. Murine models of Helicobacter ‐induced gastric cancer are valuable tools for investigating the mechanisms responsible for the stepwise pathological changes of chronic atrophic gastritis, intestinal metaplasia, dysplasia and gastric adenocarcinoma. Helicobacter felis colonization greatly accelerates the development of gastric neoplasia in mice, and causes pathologies similar to those observed with Helicobacter pylori ‐associated gastric carcinogenesis in humans. These mouse models are therefore useful for investigating genetic and environmental factors that may be involved in the pathogenesis and treatment of gastric cancer. Detailed in these protocols are procedures for inducing Helicobacter ‐associated carcinogenesis in mice as well as the histological analysis and interpretation of gastric pathology in these animals. © 2015 by John Wiley & Sons, Inc.